Pension Funds and Sustainable Investment: Challenges and Opportunities - Brett Hammond; Raimond Maurer; Olivia Mitchell (Oxford University Press, 2023)
Since its green shoots first emerged around 50 years ago, acceptance of environmental, social, and governance (ESG) considerations in institutional investing—especially in pension funds—has evolved with distinct shifts in investor preferences. This Pension Research Council volume traces these shifts and their implications, leading up to the present day. The book notes that investors have diverse reasons for devoting attention to ESG criteria when deciding where to invest their money. Some had religious motives, such as Quakers, who focused on values; this approach can offer some risk mitigation. Nevertheless, studies that look at whether divestment actually changes behaviors of companies show that this rarely occurs. Accordingly, this book offers a variety of distinct viewpoints from numerous countries, on whether, how, and when ESG criteria should, and should not, drive pension fund investments. Authors also find that policymakers should consider fund consolidation in private sector retirement systems, along with whether service provider incentives could be better aligned with sustainability incentives. For instance, boosting transparency in these markets would help generate better-informed policies, while providing beneficiaries with information relevant to their savings choices.
Keywords: 330; pensions; sustainable investment; ESG; environmental risk; transition risk; political risk; institutional investors